Improving Mathematical Concept Understanding Ability of Junior High School Students with Conceptual Understanding Procedures Learning Model - Wanabuliandari, Savitri; Rahmawati, Rita Aulia; Bintoro, Henry Suryo (Universitas Muhammadiyah Mataram, 2023)
Understanding concept material is the basic material for someone to solve problems. The importance of understanding concepts because it is useful in learning, thinking, reading and communicating. This study was conducted to analyze the improvement of mathematical concept understanding ability of experimental class students after using the CUPs learning model. This research was conducted in class VIII Junior high school with 30 experimental class students as research subjects. This research design uses one group ptetest-posttest design. Data collection techniques used include observation, interviews and tests. Initial data analysis used normality test, homogeneity test, and mean similarity test. Meanwhile, the final data analysis used Paired Sample T-test and N-gain test. The results showed that the mathematical concept understanding ability of experimental class students increased after using the CUPs learning model with an average N-gain value of 0.63 in the moderate category. Based on the results of the study, it can be concluded that the CUPs learning model is able to provide an increase in students' mathematical concept understanding ability.